Believing and Belonging: The Aesthetics of Media Representations of Islam and Muslims in Britain and Its Relationship to British Civil Religion - de Rooij, Laurens (Journal of religion in Europe, 2017)
Increasingly, debates are dealing with the integration and the compatibility of Islam with British values and society. Media narratives are used to conceptualise Islam in Britain. The existing protocols of religion, media, and public space characterise that environment, as well as dictating the participation of members in that space. This paper discusses how media constructions of Islam are linked to civil religion. It does so by discussing: (1) how the media’s protocols of public discourse affect the framing of religious identities; (2) how the media defines the aesthetic parameters of religious expression; (3) how the conceptualisation(s) of civil religion are used to regulate Islam in Britain. This study utilises a qualitative content analysis of media frames. Findings suggest that the aesthetic elements (media representations of Islam and Muslims) regulate Islam and Muslims through the codes and conventions (civil religion) of British society.